GR-independent down-modulation on GM-CSF bone marrow-derived dendritic cells by the selective glucocorticoid receptor modulator Compound A - Barcala Tabarrozzi, Andrés Ezequiel (2016)
Dendritic cells (DC) initiate the adaptive immune response. Glucocorticoids (GCs) down-modulate the function of DC. Compound A (CpdA, (2-(4-acetoxyphenyl)-2-chloro-N-methyl-ethylammonium chloride) is a plant-derived GR-ligand with marked dissociative properties. We investigated the effects of CpdA on in vitro generated GM-CSF-conditioned bone marrow-derived DC (BMDC). CpdA-exposed BMDC exhibited low expression of cell-surface molecules and diminution of the release of proinflammatory cytokines upon LPS stimulation; processes associated with BMDC maturation and activation. CpdA-treated BMDC were inefficient at Ag capture via mannose receptor-mediated endocytosis and displayed reduced T-cell priming. CpdA prevented the LPS-induced rise in pErk1/2 and pP38, kinases involved in TLR4 signaling. CpdA fully inhibited LPS-induced pAktSer473, a marker associated with the generation of tolerogenic DC. We used pharmacological blockade and selective genetic loss-of-function tools and demonstrated GR-independent inhibitory effects of CpdA in BMDC. Mechanistically, CpdA-mediated inactivation of the NF-κB intracellular signaling pathway was associated with a short-circuiting of pErk1/2 and pP38 upstream signaling. Assessment of the in vivo function of CpdA-treated BMDC pulsed with the hapten trinitrobenzenesulfonic acid showed impaired cell-mediated contact hypersensitivity. Collectively, we provide evidence that CpdA is an effective BMDC modulator that might have a benefit for immune disorders, even when GR is not directly targeted.